Historical approach to the substantiation of the philosophical theory of Оlympism - Peredelskiy A.A.; Mamedov A.A.; Kortunov V.V.; Donskikh K.Yu.; Kotusov D.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to based on a historical approach, substantiate the philosophical theory of Olympism. Methods and structure of the study. Scientific work is organized using the method of analyzing extensive factual information and formal logical methods, operations and modes used in constructing «proof by converse». Results and conclusions. It is shown that the values and ideals of Olympism were initially and still remain at the level of mythologemes and ideologemes; there is no thousand-year break in the holding of the Olympic Games, but, on the contrary, there is a continuity of various and original forms of Olympism; the presence and ideological character of these historical forms of Olympism prove the impossibility of the existence of the philosophy of Olympism.